Gentelligence the revolutionary approach to leading an intergenerational workforce - Gerhardt, Megan W. (Rowman & Littlefield, 2021)
"No one needs another book about how to lead Millennials-what we need is a book about harnessing the untapped potential from the diversity of thought in a multigenerational workforce. "Gentelligence" is that book. It presents a transformative way to end the generational wars once and for all"--